Numerical Simulation And Model Validation Of Oil Palm Empty Fruit Bunches Slow Pyrolysis Yield Prediction - Arina Fatharani; Yuwana Yuwana; Firmansyah Firmansyah; Evanila Silvia; Bosman Sidebang (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2026)
Purpose : This study aims to develop and validate a numerical simulation model for Oil Palm Empty Fruit Bunches (EFB) slow pyrolysis to predict biochar and liquid smoke yields within the temperature range of 400–600°C for optimizing palm oil waste conversion. Methodology : The research utilizes a first-order Arrhenius reaction kinetics approach with an activation energy (Ea) of 87.49 kJ/mol. Model validation was performed by comparing simulation results with experimental data from the latest literature (2023–2025) using RMSE, MAPE, and $R^2$ statistical metrics. Results : The simulation model demonstrates very high accuracy with an RMSE of 0.271%, MAPE of 0.74%, and $R^2$ of 0.9726 at a heating rate of 10°C/min. At an operating temperature of 450°C, the model predicts a biochar yield of 30.7% and an estimated liquid smoke yield of 18.6%. Findings : The numerical model is proven capable of precisely representing the thermal degradation process of EFB, enabling product yield prediction without intensive laboratory testing. Novelty : The use of the most recent validation datasets (last three years) and specific application to a gas-fueled slow pyrolysis model tailored for EFB characteristics. Originality : This research offers an integrative approach between kinetic simulation and specific pyrolysis device parameters, providing a practical solution for predicting waste mass conversion efficiency into value-added products. Conclusion : The developed model is valid and reliable for predicting EFB pyrolysis product yields, serving as a technical tool for the design and optimization of small-to-medium-scale pyrolysis reactors. Type of Paper: Research Article.